Phytobezoar: a rare late complication following laparoscopic sleeve gastrectomy surgery - Ben-Porat, Tair; Elazary, Ram; Goldenshluger, Ariela; Sherf-Dagan, Shiri; Grinbaum, Ronit; Beglaibter, Nahum (International Surgery Journal, 2017)
Case reports of bezoar after bariatric surgery are available to date only following Roux-en-Y gastric bypass (RYGB) and laparoscopic adjustable gastric banding (LAGB), but not following laparoscopic sleeve gastrectomy (LSG). Presented here is the first case reports of phytobezoars occurrence post LSG. Two case reports are presented. The mechanisms involved and the therapeutic implications are discussed. Case 1: A 41-year-old woman with a body mass index (BMI) of 45 kg/m2 underwent LSG surgery. Seven months postoperatively she developed significant vomiting and an upper GI gastrografin swallow study revealed a gastric bezoar, confirmed by an esophagogastroduodenoscopy (EGD). The bezoar was broken up and removed with the endoscope. Case 2: A 34-year-old woman with initial BMI of 42.7 kg/m2 was readmitted 5 years post LSG due to reflux accompanied with epigastric pain, vomiting, dysphagia and constipation. An upper GI gastrografin swallow study revealed esophageal dilatation. EGD showed a gastric phytobezoar 3x4cm size, removed by the endoscope. The lack of reports on bezoar occurrence after LSG may be related to the higher rates of stricture reported for LRYGB procedure comparing to LSG. In addition, LSG is a relatively new bariatric procedure, and the interval between surgery and detection of bezoars may be many years later. Thus, even being a rare late complication, bezoars should be suspected in LSG patients presenting with obstructive symptoms during the late post-surgery period. We recommend prompt endoscopic intervention to relieve the obstruction before parts of the bezoar migrate to the small bowel, necessitating operative intervention